A Passive Vibration Isolator Integrated a Skyhook Damper or a Groundhook Damper - Li, Kuinian (Journal of Vibration Testing and System Dynamics, 2026)
Presented in this paper is a passive vibration isolator integrated a skyhook damper or groundhook damper. The dynamic behavior of the isolator supporting a lumped mass is investigated using force and displacement transmissibility of the isolator. Force and displacement transmissibility are derived by modelling the new isolator a two-degree-of-freedom system. Numerical simulation and parameter studies of the isolator were performed. It reveals that the new isolator is a passive linear isolator, without any non-linear elements, spring or damper. However, it can bear a large static load and, at the same time, achieve greatly improved vibration isolation without employing high damping element, which is difficult to achieve in practices. Moreover, the implementation of such an isolator in practice is convenient. All these make the isolator attractive for engineering application.